Identification of a novel homozygous LAMB3 mutation in a Chinese male with junctional epidermolysis bullosa and severe urethra stenosis: A case report - Wang, Wei; Guo, Qiang; Chen, Jinshan; Zhang, Xi; Li, Chengyong; Li, Shuangping; Liang, Jialin; Hao, Chuan; Wang, Jingqi (Frontiers in Genetics, 2022)
Introduction: Epidermolysis bullosa(EB) is a skin fragility disorder that is caused by molecular aberrations in the epidermal basement membrane zone. Based primarily on the cleavage plane within the skin, EB is classified into four major subtypes: EB simplex, junctional EB (JEB), dystrophic EB, and Kindler EB. The junctional form (JEB) can lead to blistering and a variety of extracutaneous complications, including genitourinary tract involvement. Despite therapeutic progress, treatment modalities for urological complications of JEB are currently limited. Results: We present the case of a Chinese male with intermediate JEB and profound urinary tract stenosis. Due to the progression of the urinary tract stenosis, he presented with repeated urological symptoms, such as high frequency of urination, painful urination, and difficult voiding. After birth, multiple blisters on the fingers, feet, and limbs; nail dystrophies; and spare hair were noted. Mutation analysis revealed that the patient carried a homozygous frameshift mutation in the LAMB3 gene [c.1172_1179delinsTGTGTGTGCAAGGAG/p.(P391Lfs*23)]. After receiving treatment for urethral dilatation, lingual mucosa for anterior urethroplasty, and repair of urethral stricture using a ventral onlay penile skin flap, the patient still experienced a relapse of urinary tract stenosis. Finally, the patient underwent perineal urethrostomy. In contrast, his older brother with similar urological symptoms received regular urethral dilatation, and the curative effect was positive. Conclusions: Here we report on a case with a novel LAMB3 mutation that led to JEB with profound urinary tract stenosis, which has expanded our experience in the treatment of EB urological complications.